Oral manifestations of systemic fungal infections: 25-year experience in an endemic region - Flávia Akemi Nakayama Henschel; Camila Camarini; Mariliani Chicarelli da Silva; Lilian Cristina Vessoni Iwaki; Neli Pieralise; Elen de Souza Tolentino (Universidade Estadual de Maringá, 2022)
Some mycoses are endemic. They develop through hematogenous spread, causing a generalized infection, usually with secondary mucosal involvement.The aim of this observational and retrospective study was to report the prevalence and characteristics of oral lesions in patients diagnosed with systemic fungal infections (SFI) over a 25-year period in southern Brazil. Demographic (age, sex, ethnicity, occupation) and clinical (anatomical location, symptoms, histopathological diagnosis and management) data from the medical records of patients with SFI were collected from 1995 to 2019. 34 cases of SFI were found, of which 31 (91.18%) were diagnosed as paracoccidioidomycosis (PCM) and 3 (8.82%) as histoplasmosis. Men were much more affected (n = 31; 91.18%), with an average age of 46.9 years. Most patients (n = 18; 58.06%) were Caucasian; 48% (n = 15) were farm/rural workers and the most affected region was the jugal mucosa (n = 13; 25.49%) followed by the alveolar ridge (n = 12; 23.52%). All patients with histoplasmosis were immunocompetent men (mean age: 52.67 years), and the palate was the most affected. All patients underwent incisional biopsy and were referred to an infectologist. The dentist has an essential role in the recognition of SFI, whose oral manifestations may be the first sign. SFI should be included in differential diagnosis in patients from endemic areas. In addition, the inevitable human mobility and globalization make knowledge of these mycoses necessary worldwide, especially since advanced cases in immunocompromised patients can be fatal.